From the activities of the extension project "Humanization of constitutional civil law: perspectives and challenges": Humanized civil-constitutional law seen in practice - Saionara Macena de Araújo, Jaianny; Correa de Albuquerque da Costa, Ana Paula (Guará Journal, 2019)
Despite the new constitutional configuration, with the enactment of the Federal Constitution of 1988, the Civil Code of 2002 does not regu-late personal rights, although it presents advances when compared with the subrogated Civil Code. Hence the importance of the phenomenon of constitutionalisation, specially the Humanization of Civil Law, which brought a new way of facing private relations, hitherto eminently patrimonialist relations. Considering this, the objective of the present study was to describe the development of didactic-in-structional material, targeted to the dissemination of these rights within Paraiba’s public schools through cordel literature and parodies. There was an immediate integration among students and our group, as the music itself brought us closer together. The experience was enriching and rewarding, and it was possible in an effective way to give back the community XX (to give back somebody something), which is our duty as citizens, but mainly because we have the privi-lege to obtain public higher education.